Vegetative propagation of rose: effects of substrate, light and leaf persistence - Cárdenas-Navarro, Raul (2011)
The establishing of roses in hydroponic systems implies development propagation techniques that are efficient, economical and that produce homogeneous populations in a short time. In this work, were evaluated the effects of different substrates (peat, agrolite and vermiculite, a 1:1 v/v mixture of peat and vermiculite and two 1:1 v/v and 1:3 v/v mixture of gravel and coconut fiber); two levels of light (548 y 274 μmol.m-2.s-1) and leaf persistence on cutting (0, 5, 10, 15, 20 y 25 days after establishment) on rooting, root and axial bud developments of commercial variety of rose. The vermiculite had the best results, showed the highest number of cuttings alive and rooting percentage (60%). The light levels, leaf persistence as the interaction, were also significant. The highest rooting percentage, longer roots and better axial bud development was found with 548 μmol.m-2.s-1. Regarding leaf persistence on cutting was found that less than 10 days, the cuttings become necrotic and eventually died. There was also an inverse effect on root and bud development when the leaf persists more days, the root length was increased but axial bud decreased. In conclusion, for enhanced cuttings rooting success of rose, is required use vermiculite as substrate, with good light and leaf persists on cutting at least 15 days.